Ethene insertion into a palladium-acetyl bond: Crystal structure of [Pd(CH2CH2COMe)(NC5H4CO 2Me-2)(PPh3)]BF4, a novel reaction intermediate from the insertion process - Green,MJ; Britovsek,GJP; Cavell,KJ; Skelton,BW; White,AH (Chemical Communications, 1996)
From the catalytic conversion of CO and ethene to polyketone with [Pd(Me)(NC5H4CO2Me-2)- (PPh3)]BF4 1, the reaction of ethene with [Pd(COMe)(NC5H4CO2Me-2)-(PPh 3)]BF4 2 yields a rare example of an isolable product from the insertion of an unstrained alkene into a Pd-acyl bond, and the crystal structure of [Pd(CH2CH2COMe)-(NC5H4CO 2Me-2)(PPh3)]BF4 3 showing a novel square-pyramidal intermediate with a weakly interacting oxygen in the apical position.